Teachers engaged in research : inquiry into mathematics classrooms, grades 3-5 - Langrall, Cynthia W. (Teachers engaged in research., 2006)
Through the chapters in this volume we learn about the questions that capture the attention of teachers, the methodologies they use to gather data, and the ways in which they make sense of what they find. Some of the research findings could be considered preliminary, others confirmatory, and some may be groundbreaking. In all cases, they provide fodder for further thinking and discussion about critical aspects of mathematics education.